The Death of the Horse: Transforming Conceptions and Practices in Finland - Schuurman, Nora; Leinonen, Riitta-Marja (Humanimalia, 2012)
The role of the horse has changed significantly in Scandinavia as a consequence of the modernization and urbanization processes. At the same time the conceptions of horses have changed from work and hierarchy related servant and workmate to anthropomorphic and scientific animal conceptions. Consequently, the goal of the farmers, to get the work done and keep the horse and equipment fit to perform, has been replaced by the goal of leisure horse owners: a happy horse and the purpose for the horse to feel well. The ideas of human welfare have created an idea of a welfare horse.